2017
DOI: 10.1111/dom.12912
|View full text |Cite
|
Sign up to set email alerts
|

AMP‐activated protein kinase (AMPK) activator A‐769662 increases intracellular calcium and ATP release from astrocytes in an AMPK‐independent manner

Abstract: Aim:To test the hypothesis that, given the role of AMP-activated protein kinase (AMPK) in regulating intracellular ATP levels, AMPK may alter ATP release from astrocytes, the main sources of extracellular ATP (eATP) within the brain. Materials and Methods:Measurements of ATP release were made from human U373 astrocytoma cells, primary mouse hypothalamic (HTAS) and cortical astrocytes (CRTAS) and wild-type and AMPK α1/α2 null mouse embryonic fibroblasts (MEFs). Cells were treated with drugs known to modulate AM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…Immunocytochemistry confirmed that mature cultures contained >99% GFAP-immunoreactive glial cells (supplementary Figure S1). As previously described (Vlachaki Walker et al, 2017), cultures were maintained in Dulbecco's Modified Eagle's Media (DMEM) containing 25 mM glucose and supplemented with 10% vol/vol fetal bovine serum ([FBS] Seralabs; UK), 200 U/ml penicillinstreptomycin and 8 mM L-glutamine. Cultures were maintained in a humidified incubator at 37 C with 5% CO 2 .…”
Section: Primary Astrocyte Isolation and General Cell Culturementioning
confidence: 99%
“…Immunocytochemistry confirmed that mature cultures contained >99% GFAP-immunoreactive glial cells (supplementary Figure S1). As previously described (Vlachaki Walker et al, 2017), cultures were maintained in Dulbecco's Modified Eagle's Media (DMEM) containing 25 mM glucose and supplemented with 10% vol/vol fetal bovine serum ([FBS] Seralabs; UK), 200 U/ml penicillinstreptomycin and 8 mM L-glutamine. Cultures were maintained in a humidified incubator at 37 C with 5% CO 2 .…”
Section: Primary Astrocyte Isolation and General Cell Culturementioning
confidence: 99%
“…Mitochondrial oxygen consumption rates (OCR) were measured using the XF e 96 Agilent Seahorse Extracellular Flux analyzer, as previously described (28). See supplemental methods for additional details.…”
Section: Methodsmentioning
confidence: 99%
“…Cells were grown in 96-well plates overnight and intracellular ATP concentrations were measured using the ATPlite two-step assay (PerkinElmer, UK) as per manufacturer’s instructions and as previously described (28).…”
Section: Methodsmentioning
confidence: 99%
“…Cellular protein was isolated as previously described [24] with minor modifications. Briefly, for acute studies 450,000 cells, or for recurrent studies 250,000 cells were seeded on to 60 mm petri dishes and harvested at the end of experiments in 65 μl of lysis buffer.…”
Section: Methodsmentioning
confidence: 99%
“…Total ATP levels were measured using ATPlite (Perkin Elmer; #6016941) with minor modifications as previously described [24]. ATP/ADP ratios were assayed by luminescence assay (Sigma; #MAK135).…”
Section: Methodsmentioning
confidence: 99%